Reverse genetics in virology: A double edged sword - Hongyu Chen; Hongqi Liu; Xiaozhong Peng (Elsevier, 2022)
Reverse genetics via targeted modification of gene sequences to obtain a phenotype and the inference of a gene's function or regulatory mechanism is widely used as a potent tool in viral biology and application. However, while reverse genetics has contributed significantly to our understanding of molecular biology and the pathogenesis of viruses, its accessibility (operation) and openness (data) have raised many concerns regarding biosafety and biosecurity. In this review, we retrospectively examine the development of reverse genetics and its applications in virology, then emphasize global biosafety and biosecurity concerns regarding reverse genetics, and summarize global regulations, governance, and laws on reverse genetics. This review seeks to enhance our understanding and rational application of reverse genetics technology for the benefit of humankind.